Ziba Mir-Hosseini Thoughts : Gender and Punishment for Adultery in Islamziba Mir-Hosseini Thoughts : Gender and Punishment for Adultery in Islam - Nova Yanti Maleha; Waldi Nopriansyah; Dwi Noviani (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Ziba Mir-Hosseini is a Muslim feminist fighter, he examines how misogynistic verses often exclude women. So far, women are considered inferior to men as superior, especially when it comes to imposing sanctions for adulterers, women are more likely to become victims of gender injustice. Therefore, this article discusses the thoughts of Ziba Mir-Hosseini. This type of research is qualitative in the form of literature research with a normative approach. The author concludes that women are always considered inferior and there is no gender justice, besides that punishments in Islam place women in a discriminatory position such as punishment for female adulterers. Therefore, Ziba gives advice to Muslim scholars and thinkers to study using a feminist approach or a gender approach, both as a theory and as an analytical tool in the study of Islamic studies.